The fast radio burst population evolves, consistent with the star formation rate. Issue 1 (27th October 2021) - James, C W; Prochaska, J X; Macquart, J-P; North-Hickey, F O; Bannister, K W; Dunning, A
ABSTRACT: Fast radio bursts (FRBs) are extremely powerful sources of radio waves observed at cosmological distances. We use a sophisticated model of FRB observations – presented in detail in a companion paper – to fit FRB population parameters using large samples of FRBs detected by ASKAP and Parkes, including seven sources with confirmed host galaxies. Our fitted parameters demonstrate that the FRB population evolves with redshift in a manner consistent with, or faster than, the star formation rate (SFR), ruling out a non-evolving population at better than 98 per cent CL (depending on modelling uncertainties). Our estimated maximum FRB energy is _10 E_max [erg] = 41.70_-0.06^+0.53 (68 per cent CL) assuming a 1 GHz emission bandwidth, with slope of the cumulative luminosity distribution γ =-1.09_-0.10^+0.14 . We find a log-mean host DM contribution of 129_-48^+66 pc cm −3 on top of a typical local (interstellar medium and halo) contribution of ∼80 pc cm −3, which is higher than most literature values. These results are insensitive to assumptions of the FRB spectral index, and are consistent with the model of FRBs arising as the high-energy limit of magnetar bursts, but allow for FRB progenitors that evolve faster than the SFR.